PENGARUH FAKTOR KEUANGAN DAN NON KEUANGAN TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN - Syarifah, Atika Noor; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of financial condition, firm size, company growth,leverage, audit opinion and previous year audit reputation to the provision of going concern audit opinion. Thepopulation is all non-financial companies whichare listed in Indonesia Stock Exchange (IDX) in 2012-2015periods which have been audited and published. The sample selection has been done by using purposivesampling. Based on the predetermined criteria, 108 companies have been selected as samples. The logisticregression method and the SPSS (Statistical Product and Service Solutions) instrument has been applied toexamine the hypothesis. After the data analysis has been carried out, it has been found thatfirm size, companygrowth, leverage, audit reputation do notgive any significant influenceto the provision of going concern opinion.Meanwhile the financial condition which is proxy by the Altman Z-Score model and previous year audit opiniongive significant influence to the provision of going concern audit opinion.Keywords: Financial Ratios, Previous Year Audit Opinion, Audit Reputation, Going Concern Audit Opinion